2013
DOI: 10.1097/htr.0b013e3182795045
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in N-Acetylaspartate Following Concussion May Be Coupled to Decrease in Creatine

Abstract: Objectives:To assess the time course changes in N-acetylaspartate (NAA) and creatine (Cr) levels in the brain of athletes who suffered a sport-related concussion. Participants: Eleven nonconsecutive athletes with concussive head injury and 11 sex-and age-matched control volunteers Main outcome measures: At 3, 15, 30, and 45 days postinjury, athletes were examined by proton magnetic resonance spectroscopy for the determination of NAA, Cr, and choline (Cho) levels. Proton magnetic resonance spectroscopic data re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 51 publications
(130 reference statements)
1
54
1
Order By: Relevance
“…For example, magnetic resonance spectroscopy (MRS) studies have demonstrated neurometabolic changes after SRC lasting up to 1 month postinjury. [6][7][8][9] Similarly, in a functional MRI study, hyperactivation of the dorsolateral prefrontal cortex was found to persist beyond 2 months postinjury in athletes whose symptoms subsided at 2 weeks after injury. 10 DTI studies demonstrating structural changes from repetitive concussive head impacts have been reported in ice hockey players over the course of a single season, 11 in athletes with prolonged symptoms, 12 as well as in adolescents exhibiting close-to-normal scores on the Sports Concussion Assessment Tool (SCAT2) 13 at 2 months postinjury.…”
Section: Introductionmentioning
confidence: 86%
“…For example, magnetic resonance spectroscopy (MRS) studies have demonstrated neurometabolic changes after SRC lasting up to 1 month postinjury. [6][7][8][9] Similarly, in a functional MRI study, hyperactivation of the dorsolateral prefrontal cortex was found to persist beyond 2 months postinjury in athletes whose symptoms subsided at 2 weeks after injury. 10 DTI studies demonstrating structural changes from repetitive concussive head impacts have been reported in ice hockey players over the course of a single season, 11 in athletes with prolonged symptoms, 12 as well as in adolescents exhibiting close-to-normal scores on the Sports Concussion Assessment Tool (SCAT2) 13 at 2 months postinjury.…”
Section: Introductionmentioning
confidence: 86%
“…It is important, therefore, to consider that three studies suggest Cr alterations in mTBI (163)(164)(165). Elevated Cr was found in the centrum semiovale and corpus callosum (163,164), while decreased levels were reported in frontal WM (165). Interestingly, both groups showed normalization of these abnormalities over time, a behavior similar to that of NAA.…”
Section: State Of the Art: Mr Imaging Applications In Mild Traumatic mentioning
confidence: 96%
“…Levels of Cr, a marker of energy metabolism, are often used as the denominator in metabolic ratios, as they are assumed to vary less than the other metabolites (162). It is important, therefore, to consider that three studies suggest Cr alterations in mTBI (163)(164)(165). Elevated Cr was found in the centrum semiovale and corpus callosum (163,164), while decreased levels were reported in frontal WM (165).…”
Section: State Of the Art: Mr Imaging Applications In Mild Traumatic mentioning
confidence: 99%
“…2,3 mTBI often presents without any of the more apparent structural abnormalities seen in moderate and severe brain injury; 1 however, there is a growing body of evidence that shows that single concussive episodes are associated with subtle alterations in brain structure [4][5][6][7][8][9] and function. [10][11][12][13] mTBI differs from moderate and severe TBI in that large focal lesions do not contribute to the mechanism of injury in mTBI.…”
mentioning
confidence: 99%